Limfopenia dan Rasio Neutrofil-Limfosit pada Infeksi Severe Acute Respiratory Syndrome Coronavirus 2 - Hevrina Yufani; Rikarni Rikarni; Zelly Dia Rofinda (Jurnal Kesehatan Andalas, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can cause cytokine storm characterized by the excessive release of pro-inflammatory cytokines, leading to lymphopenia and neutrophilia. Lymphopenia and high Neutrophil-Lymphocyte Ratio (NLR) on admission were associated with the severity of the disease. Objectives: To found out lymphopenia and high NLR in SARS-CoV-2 infection. Methods: This was a cross-sectional descriptive study on all patients infected with SARS-CoV-2 who met the inclusion and exclusion criteria at Dr. M. Djamil Hospital Padang from March until August 2020. Lymphocyte count and neutrophil count on admission were examined by flowcytometry method and NLR was calculated. Lymphopenia is a lymphocyte count of <1.5x103/mm3 and high NLR is ≥ 3.13.  Results: The study samples were 123 patients, with 58.5% women. The mean age was 47.80 (15.59) years. Lymphopenia was present in 39% of patients with mean lymphocyte count was 1.84 (0.83) x103/mm3. High NLR was present in 48% of patients with a mean NLR was 5.06 (4.87). Conclusion: Lymphopenia was present in 39% of patients infected with SARS-CoV-2 and high NLR was present in 48% of patients infected with SARS-CoV-2.Keywords:  lymphopenia, neutrophil-lymphocyte ratio, SARS-CoV-2